Thermal management of electronics: An experimental analysis of triangular, rectangular and circular pin-fin heat sinks for various PCMs. (August 2018) - Ali, Hafiz Muhammad; Ashraf, Muhammad Junaid; Giovannelli, Ambra; Irfan, Muhammad; Irshad, Talal Bin; Hamid, Hafiz Muhammad; Hassan, Faisal; Arshad, Adeel
Highlights: Optimization of heat transfer in a compact portable device using PCM and TCE. Study of comparison between rectangular, round and triangular pin fins. PCM based heat sink design for heat input between 5 W and 8 W. Comparison of PCMs based upon Stefan number and heat storage ratio. Abstract: This study implies experimental investigation for optimization of heat transfer in electronic integrated circuits using close packed phase change materials (PCMs) filled pin - fin heat sinks. The aim of this study is to find the most efficient pin - fin configuration filled with optimum PCM to extend the operating range of electronic circuits. The experimental methodology is based upon variation of pin - fin configurations in rectangular, round and triangular cross-sections. Each configuration is allowed a pin - fin volumetric percentage of 9%. For analysis using PCM a volume fraction of 90% is maintained and six PCMs with different thermo-physical properties (varying melting temperatures, latent heats and heat capacities) are selected. These include paraffin wax, RT-54, RT-44, RT-35HC, SP-31 and n-eicosane . Moreover, the power levels mimicking heat input range between 5 W and 8 W. The resulting information is analyzed for the performance of a heat sink with and without PCM. Besides that, PCM ascendency is manipulated in terms of operational time, enhancement ratios, Stefan number and storage ratio. The outcomes suggest that triangular pin-fins are found to be the most effective pin - fin configuration for heat transfer both with and without PCM.